Effective and Safe Daclatasvir Drug Exposures Predicted in Children Using Adult Formulations. Issue 12 (27th July 2021) - Cressey, Tim R.; Abbassi, Maggie; Lallemant, Marc; Indolfi, Giuseppe; Al-Nahari, Mogeb; Farid, Samar; Penazzato, Martina; Easterbrook, Philippa; El-Sayed, Manal H.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Sofosbuvir (SOF)/daclatasvir (DCV) is the direct-acting antiviral regimen of choice in many low- and middle-income countries for curative treatment of chronic hepatitis C virus (HCV) infection in adults, but data on the use of DCV in children are lacking. We performed a population pharmacokinetic (PK) analysis to predict DCV exposure in children treated with available adult formulations. Methods: DCV concentration data from HCV-infected adolescents receiving SOF/DCV [400/60 mg, once daily (OD)] who participated in a PK study in Egypt were used for model development. PK parameters were estimated using a population approach. Monte Carlo simulations were run for virtual children weighing 10 to <35 kg receiving 60 or 30 mg OD, and DCV exposures were compared with adults ranges. Results: Seventeen HCV-infected adolescents (13 males) provided 151 DCV concentrations. Median (range) age was 14 (11–18) years and weight 50 (32–63) kg. In these adolescents receiving 60 mg DCV, median (interquartile range) DCV area under the concentration time curve 0 to 24 hours, maximum concentrations, and minimum concentrations were 11, 130 (8140–14, 690) ng·h/mL, 1030 (790–1220) ng/mL and 130 (110–220) ng/mL, respectively, compared with 10, 343 (7661–14, 095) ng·h/mL, 1132 (876–1518) ng/mL and 110 (55.7–192) ng/mL predicted in children 10 to <35 kg receiving 30 mg. The proportion of children with DCV exposures above the adult range rapidly increased for children <30 kg using 60 mg OD, similarly for children 10–14 kg using 30 mg. Conclusions: DCV 30 mg OD was predicted to achieve effective and safe exposures in children 14 to <35 kg, perhaps down to 10 kg. These results should be validated clinically. Low-cost available adult DCV formulations together with approved pediatric doses of SOF would expand global access to HCV treatment for children.